Education and the UN Development Goals Projects (MDGs and SDGs): Definitions, Links, Operationalisations. (April 2022) - Kushnir, Iryna; Nunes, Ana
The United Nations (UN) has orchestrated a mobilisation of the world community over the past 20 years, to tackle a range of global problems via two consecutive development projects: the Millennium Development Goals (MDGs) and the Sustainable Development Goals (SDGs). Research focused on education in these projects is fragmented, with apparent gaps in knowledge around: i) the definition of education; ii) the links between the education goal and other goals; and iii) the operationalisation of those links. The originality of this study rests in addressing these interrelated gaps, by drawing on the soft governance approach and thematic analysis of 12 key UN policy documents. The findings explain the position of education in both UN projects by highlighting important aspects of its dynamic nature. First, the definition of education has been evolving, along with its links to the different themes covered in both MDG and SDG projects. Second, certain aspects of the process of operationalisation of education remain vague—the UN must work towards clarification of these remaining aspects if the operationalisation of education for sustainable development is to be improved. The significance of these findings is in engendering directions for international policy-making in the upcoming world summits, leading up to the 2030 deadline for the achievement of the SDGs, and in highlighting the fact that education should increasingly be regarded as an indispensable tool for policy-makers involved in this process.